Alterações posturais e sintomas depressivos em puérperas - Lima, Maria do Carmo Correia de (2014)
The postpartum period, also know as postpartum, is a time of great physical and psychological changes, increasing the risk for onset of musculoskeletal discomfort, postural changes and depressive symptoms, which are directly related to muscle and physiological functions and may affect function and the musculoskeletal control, reflecting the postural pattern. In clinical practice, postural changes are frequently observed among the mothers, both either due to biomechanical compensations during pregnancy or the tensions and burdens generated by baby care. In the literature, there are few studies that relate postural alignment and depressive symptoms. This relationship will add up to knowledge that helps identify the obstacles to recovery and lead to the development of strategies and targeted interventions for postpartum women. The objective of the study is to investigate depressive symptoms in postpartum women, and the influence of this posture. Eighty women were evaluated; with postpartum time of two to 30 weeks; pregnancy with resolution between 34 and 42 weeks and calving and healthy live baby. Depressive symptoms were screened through Depression Scale Edinburgh Postnatal (EPDS). Postural assessment was conducted through computerized photogrammetry and visual. Approximately 33% (n = 26) of evaluated postpartum women had scores indicating postpartum depression. Postpartum women showed distinct global postural patterns in relation to depressive symptoms and these compensation patterns generated in the body segments, more significantly in the pelvis.